Cannabinoid Modulation of Memory Consolidation in Rats: Beyond the Role of Cannabinoid Receptor Subtype 1 - Ratano, Patrizia; Palmery, Maura; Trezza, Viviana; Campolongo, Patrizia (Frontiers in Pharmacology, 2017)
The effects induced by exogenous manipulation of endocannabinoid neurotransmission on emotion and memory are often contradictory. Among the different factors involved, of particular interest is the binding affinity of endocannabinoids, and their analogues, for other receptor families beyond cannabinoid receptors, such as the peroxisome proliferator-activated receptors (PPARs), and the transient receptor potential cation channel subfamily V member 1 (TRPVs). The aim of this study was to investigate which receptor subtype mediates cannabinoid effects on memory consolidation for emotionally arousing experiences. We tested two cannabinoid compounds with different pharmacological properties in the inhibitory avoidance task, and evaluated whether the observed effects are mediated by cannabinoid, PPARα or TRPV1 receptor activation. We found that the synthetic cannabinoid agonist WIN55,212-2 and the FAAH inhibitor URB597 both enhanced memory consolidation for inhibitory avoidance training. WIN55,212-22 effects on memory consolidation were predominantly mediated by CB1 receptor activation but CB2 receptors were involved as well. The URB597-induced memory enhancement was dependent on the activation not only of CB1 and CB2 receptors but, notwithstanding, PPAR-α and TRPV1 receptors were involved as well. Our findings drive beyond the classical hypothesis centered on the unique role of CB1 receptor activation for cannabinoid effects on memory, and reveal new insights in the neural mechanisms of memory consolidation.